GAYA KEPEMIMPINAN DAN KERJASAMA TIM TERHADAP PENERAPAN TOTAL QUALITY MANAGEMENT : STUDI KASUS PADA PT. NOVARTIS NUTRITION SURABAYA - Sungkowo Winarto; Pompong B Setiadi; Sri Rahayu (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2022)
The application of Total Quality Management or total quality management in an organization with the aim of continuous quality improvement cannot be separated from the leadership style and teamwork applied to the organization. The objectives to be achieved in this study are to determine simultaneously the variables of leadership style and teamwork affect the implementation of Total Quality Management, partially the variables of leadership style and teamwork affect the implementation of Total Quality Management and the dominant influence of these variables. on the implementation of Total Quality Management. The type of data used in this research is cross section because it collects data at a certain time (questionnaire distribution). F count (258.356) > F table (3.09), then Ho is rejected and Hi is accepted, which means simultaneously or all independent variables, namely leadership style and teamwork, significantly affect the dependent variable, namely total quality management. t count of 5.955 and t table of 1.985. Because t count > t table, then Ho is accepted at the level of significant 5%. So partially leadership style has a significant effect on total quality management. t count is 8.022 and t table is 1.985. Because t count > t table, then Ho is accepted at the level of significance 5%. So partially teamwork has a significant effect on total quality management. teamwork variable is the most dominant variable in influencing Total Quality Management. This can be seen from the largest value of , which is 0.643